Analisi terminologica dei siti web delle Compagnie Aeree British Airways, Alitalia, Tam e LAN (Altre Modernità, 2012)
This study is part of a research about the terminology found in the language of tourism, defined as an area of ??knowledge. It has been conducted a study based upon the terms used by four major international airlines - two from Europe: British Airways (United Kingdom) and Alitalia (Italy), and two from Latin America: TAM (Brazil) and Lan (Chile) - in their websites, designed for the final consumer (passenger), since each of them has a different official language (English, Italian, Portuguese and Spanish, respectively). The specific objectives were: i) to reflect about the differences among the terms used by each airline, ii) to analyze whether there is a substantial presence of acronyms, iii) to identify how each of these airlines use English, considering that only the first one has it as its official language. The hypothesis that have guided the research are: i) there are no significant changes among the terminology used by the airlines which are the object of the present research, ii), there is a fair use of synonyms for the same concepts, iii) there is an extensive use of acronyms, iv) there is a considerable influence of English, that may be seen in language borrowings and in some hybrid formations.